PENGARUH NILAI PERUSAHAAN, PROFITABILITAS DAN RISIKO KEUANGAN TERHADAP EARNINGS MANAGEMENT - Agustin, Trisia; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to analyze the influence of firm value, profitability, and financialrisk to the earnings management on consumption goods industrial sector manufacturing companies in IndonesiaStock Exchange. The collection of sample are 21 companies with the observation period from 2009 to 2012, so 84observation data have been obtained. The source of secondary data is originated from Indonesia Stock Exchangeand the official website of Indonesia Stock Exchange, http:/www.idx.co.id. The data analysis technique is carriedout by using the multiple linear regressions analysis with the assistance of SPSS program. Based on the result ofthe analysis, it can be conculeded that: (1) firm value has significant influence to the earnings management onconsumption goods industrial sector manufacturing companies in Indonesia Stock Exchange; (2) Profitabilityhas significant influence to the earnings management on consumption goods industrial sector manufacturingcompanies in Indonesia Stock Exchange; (3) Financial risk has significant influence to the earnings managementon consumption goods industrial sector manufacturing companies in Indonesia Stock ExchangeKeywords: firm value, profitability, financial risk and earnings management